Stereotactic radiotherapy in neovascular age-related macular degeneration: Real-life efficacy and morphological evaluation of the outer retina-choroid complex. Issue 52 (December 2016) - Ranjbar, Mahdy; Kurz, Maximilian; Holzhey, Annekatrin; Melchert, Corinna; Rades, Dirk; Grisanti, Salvatore
Abstract : Abstract: Stereotactic radiotherapy (SRT) is a new approach to treat neovascular age-related macular degeneration (nAMD). The INTREPID trial suggested that SRT could reduce the frequency of regular intravitreal injections (IVIs) with antivascular endothelial growth factor drugs, which are necessary to control disease activity. However, the efficacy of SRT in nAMD and resulting morphological changes have not been validated under real-life circumstances, an issue, which we would like to address in this retrospective analysis. Patients who met the INTREPID criteria for best responders were eligible for SRT. A total of 32 eyes of 32 patients were treated. Thereafter, patients were examined monthly for 12 months and received pro re nata IVI of aflibercept or ranibizumab. Outcome measures were: mean number of injections, best-corrected visual acuity, and morphological changes of the outer retina-choroid complex as well as patient safety. Mean number of IVI decreased by almost 50% during the 12 months after SRT compared to the year before, whereas visual acuity increased by one line (logMAR). Morphological evaluation showed that most changes affect outer retinal layers. Stereotactic radiotherapy significantly reduced IVI retreatment in nAMD patients under real-life circumstances. Therefore, SRT might be the first step to stop visual loss as a result of IVI undertreatment, which is a major risk.